On Weak Symmetries of Generalized Sasakian-Space-Forms - Prakasha, D.G.; Chavan, Vasant (Communications in Mathematics and Applications, 2014)
The purpose of the paper is to study weakly symmetric and weakly Ricci-symmetric generalized Sasakian-space-forms. We consider the locally symmetric and recurrent type of weakly symmetric generalized Sasakian-space-forms. Also, locally Ricci-symmetric and Riccirecurrent weakly Ricci-symmetric generalized Sasakian-space-forms are discussed.